2013
DOI: 10.1080/03632415.2013.848343
|View full text |Cite
|
Sign up to set email alerts
|

Catfish Sampling Techniques: Where We Are Now and Where We Should Go

Abstract: We review the peer‐reviewed literature regarding sampling of the three most commonly managed ictalurids: Channel Catfish, Blue Catfish, and Flathead Catfish. For each species, we summarize what is known about data quality (accuracy and precision) and sampling efficiency of the most commonly used gears for surveying these species. We identify research needs and provide information to guide gear selection based on different sampling objectives. To rank gear‐specific sampling efficiency (catch/h and catch/person‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
121
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(128 citation statements)
references
References 43 publications
6
121
1
Order By: Relevance
“…Further complicating a trotline standard is the wide variety of hook styles from which to choose (e.g., Kahle, circle, Limerick), which may affect catch bias and mortality (Ott & Storey 1991). Our results agree with other studies that have found trotlines capture larger individuals, but we did not assess accuracy of our results (sensu Bodine et al 2013), we compared relative differences between trotlines and baited tandem hoop nets, which have been used in this system before (Stewart & Long 2012;Stewart 2013).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Further complicating a trotline standard is the wide variety of hook styles from which to choose (e.g., Kahle, circle, Limerick), which may affect catch bias and mortality (Ott & Storey 1991). Our results agree with other studies that have found trotlines capture larger individuals, but we did not assess accuracy of our results (sensu Bodine et al 2013), we compared relative differences between trotlines and baited tandem hoop nets, which have been used in this system before (Stewart & Long 2012;Stewart 2013).…”
Section: Discussionsupporting
confidence: 79%
“…Thus, the cautionary statement to using Zote TM soap as a bait seems unwarranted with reference to increased phosphorous loading. Many previous studies have investigated bait type for use in hoop nets (e.g., Flammang & Schultz 2007;Wallace et al 2011;Bodine et al 2013) and we hope the results of this study spurs additional research regarding the use of soap, such as Zote TM , as bait. Moreover, we hope further research investigating the use of trotlines baited with soap will be initiated as it appears to hold promise for sampling channel catfish specifically with negligible bycatch, particularly aquatic turtles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximum catch rates in lotic systems have been achieved during summer months, when water temperatures exceed 20 C and water levels were low (Quinn 1986;Travnichek 2011); however, sampling conditions relative to efficiency have not been evaluated for lentic habitats (Bodine et al 2013). Although we did not quantify catch by habitat type, a large proportion of the flathead catfish were captured near rocky habitat.…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of flathead catfish in Lake Mitchell was similar to the nearby James River, but higher than that reported for the Big Sioux River in South Dakota (Arterburn 2001). Electrofishing catches for lentic systems on average are higher than for lotic systems (Bodine et al 2013) and a chase boat was not employed to do the river sampling (Arterburn 2001).…”
Section: Discussionmentioning
confidence: 99%